Comparison of chemiluminescent heterogeneous and homogeneous-heterogeneous assays coupled with isothermal circular strand-displacement polymerization reaction amplification for the quantification of miRNA-141 - Solovjev, Anton M; Galkin, Ivan I; Medved'ko, Alexey V; Pletjushkina, Olga Yu; Zhao, Shulin; Sakharov, Ivan Yu (Analyst (London), 2022)
Heterogeneous and homogeneous-heterogeneous assays for the quantitation of hsa-miR-141-3p (miRNA-141) were constructed. Both microplate assays were based on the use of the isothermal circular strand-displacement polymerization reaction (ICSDPR), which was carried out in heterogeneous and homogeneous media, respectively. In addition, a streptavidin-polyperoxidase conjugate and enhanced chemiluminescence were used to increase the assay's sensitivity. A comparison of the developed assays showed that the sensitivity of the heterogeneous assay was higher than that of the homogeneous-heterogeneous assay. The detection limit values of the heterogeneous and homogeneous-heterogeneous assays were 51 fM and 10 pM, respectively. The amplification index for the ICSDPR used in the heterogeneous assay of miRNA-141 was 100. Using miRNAs of the miRNA-200 family, the high specificity of the assay was demonstrated. MiRNA-141 in human cultured cells was determined by the heterogeneous ICSDPR-assisted assay with chemiluminescence detection. To assess the purification yield of miRNAs from cellular lysates, the heterogeneous assay of miRNA-39 developed on the same platform was used. The intracellular content of miRNA-141 in Caco-2, HepG2, MCF-7 and HeLa was shown to be 3400, 1400, 1300 and 470 copies per cell, respectively. A heterogeneous and homogeneous-heterogeneous chemiluminescent microplate assay was developed for the determination of miRNA-141 levels in human cells.